Aplicación de brasinoesteroides y sus análogos en pasto Janeiro (Erioclhoa polystachya) en el cantón Babahoyo - Provincia de Los Ríos - Gavilánez Paredes, Carlos Luis (2020)
This research work was carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road. The geographical coordinates in UTM were X: 1.7723946; Y: 79.7102593. The area has a humid tropical climate, with a temperature that ranges between 24 and 26 ° C, with relative humidity of 88%, average annual rainfall of 1262 mm, with a height of 8 meters above sea level and 990 hours of annual average heliophany. As evaluation material we used janeiro grass plants. In this investigation, a "Random Complete Blocks" Design was used, with five treatments and four repetitions, the variables evaluated were: plant length, leaf length, leaf width, leaf area, stem diameter, number of leaves , wet weight yield, dry weight yield, dry matter yield percentage (RMS). In the present investigation, it was determined that as the age of the pasture Janeiro (Eriochloa polystachya) advanced, forage production increased in the T3 treatment (Gibberellic acid + Indol-3-ylacetic acid + Brassinolide 30 g / ha) the same as it was assimilated in a better way by the plant. Treatment T3 (Gibberellic acid + Indol-3-ylacetic acid + Brassinolide 30 g / ha) showed highly significant statistical differences in number of leaves, dry weight with respect to T5 (0 Kg / ha) that was the control with dose 0 Regarding the agronomic variables: leaf width, stem diameter, wet weight, they did not show statistical significance and the results show that the T5 treatment (0 Kg / ha presented numerically the lowest averages. Apply a fertilization program based on hormonal products, substantially affects the behavior and performance of pasture Janeiro in the evaluation area.